Relationship between urodynamic findings and sexual function in multiple sclerosis patients with lower urinary tract dysfunction. (19th November 2014) - Fragalà, E.; Russo, G. I.; Di Rosa, A.; Giardina, R.; Privitera, S.; Favilla, V.; Castelli, T.; Chisari, M.; Caramma, A.; Patti, F.; Cimino, S.; Morgia, G.
<x xml:space="preserve">Abstract</x> Background and purpose Sexual dysfunction (SD) is prevalent in multiple sclerosis (MS) patients and affects quality of life. Furthermore, lower urinary tract dysfunction (LUTD) is common in MS patients. Our aim was to determine the relationship between urodynamic findings and SD in a cohort of MS patients with LUTD. Methods From January 2011 to September 2013, 135 consecutive patients with MS in remission phase and LUTD underwent a first urodynamic examination, according to the International Continence Society criteria. Neurological impairment was assessed using the Expanded Disability Status Scale and SD was investigated with the Female Sexual Function Index (FSFI) or the International Index of Erectile Function (IIEF‐15). Multivariate logistic regression analysis was performed to identify predictors of female SD (FSFI < 26.55) or moderate−severe erectile dysfunction (ED) (IIEF‐EF ≤ 16), after adjusting for confounding factors including urodynamic findings. Results Subjects with maximum detrusor pressure during involuntary detrusor contraction (PdetmaxIDC) ≥20.0 cmH2O had lower IIEF‐EF, IIEF overall satisfaction (IIEF‐OS), FSFI‐Arousal, FSFI‐Lubrication and FSFI‐Orgasm. Subjects with maximum cystometric capacity (MCC) ≥135 ml had higher IIEF‐EF, intercourse satisfaction (IIEF‐IS), orgasmic function (IIEF‐OF), sexual desire (IIEF‐SD), FSFI‐Arousal, FSFI‐Lubrication, FSFI‐Orgasm, FSFI‐Satisfaction and FSFI‐Pain. On multivariate logistic regression analysis, PdetmaxIDC ≥20 cmH2O [odds ratio (OR) 6.7; P < 0.05] and MCC <135 ml (OR 6.80; P < 0.05) were predictors of moderate−severe ED. In a model including all previous variables, compliance ≤3 ml/cmH2O was an independent predictor of moderate−severe ED (OR 14.49; P < 0.01). No relationship was found between the previous variables and FSFI <26.55. Conclusions Neurogenic bladder is associated with SD in MS patients. The presence of PdetmaxIDC ≥20 cmH2O, MCC <135 ml and compliance ≤3 ml/cmH2O may significantly predict the presence of moderate−severe ED.